Identification of environmentally stable QTLs controlling Saponin content in Glycine max - Teraishi, Masayoshi (Breeding science, 2017)
Saponins are secondary metabolites that are widely distributed in plants. There are two major saponin precursors in soybean: soyasapogenol A, contributing to the undesirable taste, and soyasapogenol B, some of which have health benefits. It is important to control the ratio and content of the two major saponin groups to enhance the appeal of soybean as a health food. The structural diversity of saponin in the sugar chain composition makes it hard to quantify the saponin content. We measured the saponin content in soybean by removing the sugar chain from the saponin using acidic hydrolysis and detected novel quantitative trait loci (QTLs) for saponin content. Major QTLs in the hypocotyl were identified on chromosome 5 near the SSR marker, Satt 384, while those in the cotyledon were on chromosome 6 near Sat_312, which is linked to the T and E1 loci. Our results suggest that saponin contents in the hypocotyl and cotyledon are controlled by different genes and that it is difficult to increase the beneficial group B saponin and to decrease the undesirable group A saponin at the same time